Inhibition of IAPP Aggregation and Toxicity by Natural Products and Derivatives. (15th November 2015) - Pithadia, Amit; Brender, Jeffrey R.; Fierke, Carol A.; Ramamoorthy, Ayyalusamy
Abstract : Fibrillar aggregates of human islet amyloid polypeptide, hIAPP, a pathological feature seen in some diabetes patients, are a likely causative agent for pancreatic beta-cell toxicity, leading to a transition from a state of insulin resistance to type II diabetes through the loss of insulin producing beta-cells by hIAPP induced toxicity. Because of the probable link between hIAPP and the development of type II diabetes, there has been strong interest in developing reagents to study the aggregation of hIAPP and possible therapeutics to block its toxic effects. Natural products are a class of compounds with interesting pharmacological properties against amyloids which have made them interesting targets to study hIAPP. Specifically, the ability of polyphenolic natural products, EGCG, curcumin, and resveratrol, to modulate the aggregation of hIAPP is discussed. Furthermore, we have outlined possible mechanistic discoveries of the interaction of these small molecules with the peptide and how they may mitigate toxicity associated with peptide aggregation. These abundantly found agents have been long used to combat diseases for many years and may serve as useful templates toward developing therapeutics against hIAPP aggregation and toxicity.